PENGARUH PEMBANGUNAN RUSUNAWA KYAI MOJO TERHADAP PENANGANAN PERMUKIMAN KUMUH DI KAWASAN PESISIR - Erga Pradika (UNIVERSITAS INDO GLOBAL MANDIRI, 2014)
Flat rental housing still be used as an alternative to solve the slums, including in coastal areas. This is indicated in the strategic plan of improving the quality of the environment of the slums by the year 2002-2010 by Director General of Housing Settlement and also include in five treatment approaches to solve the slums (UN-HABITAT, 2005). However, after the implementation of flat rental housing, they still have problems unfinished arise as in the Village Jobokuto, Jepara regency. There are still many slums located around rusunawa and directly adjacent to the beach. The purpose of this study is to examine the influence and ability of flat rental housing to handle slums in coastal areas. The research approach using a quantitative approach. The analysis conducted is the analysis of changes in coastal slums, analysis of the physical characteristics and the availability of facilities to support the needs of coastal communities. The analysis tools are descriptive statistics, analysis of the ratio of the average (paired sample t test and Wilcoxon) and the overlay map. The study used a questionnaire in 65 samples, interviews and documentation of the object as the primary instrument of data collection and study of literature and instansional for secondary data collection. The findings obtained indicate that Rusunawa Kyai Mojo in the Village Jobokuto less effect on handling problems, especially in the coastal slum Village Jobokuto. The result is addressed to relevant stakeholders in order to finish the problem of slums.